Differential treatment outcomes in BRCA1/2‐, CDK12‐, and ATM‐mutated metastatic castration‐resistant prostate cancer. Issue 12 (10th March 2021) - Kwon, Daniel H.; Chou, Jonathan; Yip, Steven M.; Reimers, Melissa A.; Zhang, Li; Wright, Francis; Dhawan, Mallika S.; Borno, Hala T.; Desai, Arpita; Aggarwal, Rahul R.; Wyatt, Alexander W.; Small, Eric J.; et al.
Abstract : BACKGROUND: DNA damage repair mutations (DDRm) are common in patients with metastatic castration‐resistant prostate cancer (mCRPC). The optimal standard therapy for this population is not well described. METHODS: A multi‐institutional, retrospective study of patients with mCRPC and DDRm was conducted. Patient data, including systemic therapies and responses, were collected. The decline in prostate‐specific antigen ≥ 50% from baseline (PSA50) and overall survival (OS) from the treatment start were compared by mutation and treatment type. A multivariable Cox proportional hazards model for OS was created that controlled for DDRm, first‐line treatment received for mCRPC, and clinical factors. RESULTS: The most common DDRm observed among 149 men with mCRPC were BRCA1/2 (44%), CDK12 (32%), and ATM (15%). The majority received first‐line abiraterone (40%) or enzalutamide (30%). The PSA50 rate with first‐line abiraterone was lower for CDK12 (52%) than BRCA1/2 (89%; P = .02). After first‐line abiraterone or enzalutamide, the median OS was longest with second‐line carboplatin‐chemotherapy (38 months) in comparison with abiraterone or enzalutamide (33 months), docetaxel (17 months), or cabazitaxel (11 months; P = .02). PSA50 responses to carboplatin‐based chemotherapy were higher for BRCA1/2 (79%) than ATM (14%; P = .02) or CDK12 (38%; P = .08). In a multivariable analysis, neither the specific DDRm type nor the first‐line treatment was associated with improved OS. CONCLUSIONS: Responses to standard therapies were generally superior in patients with BRCA1/2 mutations and inferior in patients with ATM or CDK12 mutations. The DDRm type did not independently predict OS. After progression on first‐line abiraterone or enzalutamide, carboplatin‐based chemotherapy was associated with the longest OS. These findings may inform treatment discussions and clinical trial design and require prospective validation. Abstract : Patients with metastatic castration‐resistant prostate cancer (mCRPC) and DNA damage repair mutations (DDRm) have clinical outcomes and responses to treatment that vary on the basis of the specific DDRm type. Patients with CDK12 mutations have the lowest PSA50 response rates to first‐line abiraterone (where PSA50 is a decline in prostate‐specific antigen ≥ 50% from the baseline), and patients with BRCA1/2 mutations have the highest. Patients with ATM mutations have the lowest PSA50 response rates to carboplatin‐based chemotherapy, and patients with BRCA1/2 mutations have the highest.